2020
DOI: 10.1016/j.phrs.2020.104859
|View full text |Cite
|
Sign up to set email alerts
|

Candidate drugs against SARS-CoV-2 and COVID-19

Abstract: Outbreak and pandemic of coronavirus SARS-CoV-2 in 2019/2020 will challenge global health for the future. Because a vaccine against the virus will not be available in the near future, we herein try to offer a pharmacological strategy to combat the virus. There exists a number of candidate drugs that may inhibit infection with and replication of SARS-CoV-2. Such drugs comprise inhibitors of TMPRSS2 serine protease and inhibitors of angiotensin-converting enzyme 2 (ACE2). Blockade of ACE2, the host cell receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
523
0
18

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 498 publications
(542 citation statements)
references
References 115 publications
1
523
0
18
Order By: Relevance
“…In fact, this assay setup is very similar to one recently shown to work as a specific and sensitive SARS-CoV-2 surrogate virus neutralization test based on antibody-mediated blockage of this same PPI (CoV-S-ACE2) (Tan et al, 2020). With this setup in our hands, we performed a preliminary screening of representative organic dyes from our in-house library plus a few compounds that are or have been considered of possible interest in inhibiting SAR-CoV-2 by different mechanisms of action, e.g., chloroquine, clemastine, and suramin (Colson et al, 2020;da Silva et al, 2020;Gordon et al, 2020;McKee et al, 2020;Xiu et al, 2020). Screening at 5 µM indicated that most have no activity and, hence, are unlikely to interfere with the S-protein -ACE2 binding needed for viral attachment.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, this assay setup is very similar to one recently shown to work as a specific and sensitive SARS-CoV-2 surrogate virus neutralization test based on antibody-mediated blockage of this same PPI (CoV-S-ACE2) (Tan et al, 2020). With this setup in our hands, we performed a preliminary screening of representative organic dyes from our in-house library plus a few compounds that are or have been considered of possible interest in inhibiting SAR-CoV-2 by different mechanisms of action, e.g., chloroquine, clemastine, and suramin (Colson et al, 2020;da Silva et al, 2020;Gordon et al, 2020;McKee et al, 2020;Xiu et al, 2020). Screening at 5 µM indicated that most have no activity and, hence, are unlikely to interfere with the S-protein -ACE2 binding needed for viral attachment.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, there is no clinically approved drug for SARS-CoV2. However, recent publications reveal that several medications such as ivermectin, hydroxychloroquine, and remdesivir are being used to reduce the virus load and improve disease symptoms (Caly et al 2020;McKee et al 2020;Wang et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Coronaviruses are named after the protruding spike (S) glycoproteins on their envelope, giving a crown (corona in latin) shape to the virions (4). Of the four structural proteins of coronavirues, S, envelope (E), membrane (M), and nucleocapsid (N), the S protein is the one playing a key role in mediating the viral entry into the host cells (5)(6)(7), making it one of the main targets for the development of therapeutic drugs and vaccines (8)(9)(10)(11)(12)(13)(14). Comprised of two functional subunits, S1 and S2, it first binds to a host receptor through the receptor-binding domain (RBD) in the S1 subunit and then fuses the viral and host membranes through the S2 subunit (7,15).…”
Section: Introductionmentioning
confidence: 99%